Body height and its estimation utilizing arm span measurements in population of Birgunj Area of Nepal: An Anthropometric study - Sah, RP; Kumar, A; Bhaskar, RK (Journal of College of Medical Sciences-Nepal, 2014)
Background Arm span is the most reliable anthropometric measurement to predict the stature of an individual. Age and sex have to be taken into account to the best to predict height from arm span. It is useful in predicting age related loss in stature and in identifying individuals with disproportionate growth abnormalities and skeletal dysplasia. Objective The present study was under taken to measure the stature as well as arm span and to determine whether there is any correlation between the stature and the arm span Method This cross sectional type of descriptive study was carried out with a total number of 400 Nepalese adult population consisting of 225 Nepalese male adults and 175 female adults aged between 25 to 45 years. Stature and arm span were measured directly from the subjects by using anthropometric technique by a measuring tape. The data taken were statistically analyzed by computation to find out its normative value. The relationship between body height and arm span were determined using simple correlation coefficients. Then a linear regression analysis was performed to examine the extent to which arm span can readily predict body height Results The results have shown male of Birgunj are 167.39± 6.170 cm tall and have arm span of 168.01±7.659 cm, while female of Birgunj are 155.61±6.894 cm and have arm span of 159.25±6..362cm. The results obtained are substantially alike in other populations, since arm span was too close to body heights in male and greater in female. Conclusion The body height and arm span correlates well in males but not in females. This confirms the necessity for developing separate height models for each population and different sex. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 9-13 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10231